![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\sqrt{\left(x-1\right)^2}=5\Rightarrow\left(x-1\right)=\left\{5;-5\right\}\Leftrightarrow\hept{\begin{cases}x-1=5\Rightarrow x=6\\x-1=-5\Rightarrow x=-4\end{cases}}\)
b,\(3+\sqrt{x}=5\Rightarrow\sqrt{x}=2\Rightarrow x=4\)
c,\(\sqrt{x^2-2x+1}=x-1\Rightarrow\sqrt{\left(x-1\right)^2}=x-1\Rightarrow x-1=\left\{x-1;-\left(x-1\right)\right\}\)
\(\Leftrightarrow\hept{\begin{cases}x-1=x-1\Rightarrow x\in R\\x-1=-\left(x-1\right)\Rightarrow x-1=-x+1\Rightarrow x+x=1+1\Rightarrow2x=2\Rightarrow x=1\end{cases}}\)
Vậy x = 1
d, \(\sqrt{x^2-10x+25}=x+3\Rightarrow\sqrt{\left(x-5\right)^2}=x+3\Rightarrow x-5=\left\{x+3;-\left(x+3\right)\right\}\)
\(\Leftrightarrow\hept{\begin{cases}x-5=x+3\Rightarrow x-x=3+5\Rightarrow0x=8\left(loai\right)\\x-5=-\left(x+3\right)\Rightarrow x-5=-x-3\Rightarrow x+x=-3+5\Rightarrow2x=2\Rightarrow x=1\left(chon\right)\end{cases}}\)
Vậy x = 1
\(pt\Rightarrow\left(x^2+1\right)^2=\left(x+1\right)^2\left(x^2-2x+3\right)\)
\(\Leftrightarrow2\left(x^2-2x-1\right)=0\)
x2+1 = (x+1)\(\sqrt{x^2-2x+3}\)
Phân tích VP = \(\sqrt{\left(x+1\right)^2\left(x-1\right)^2+2\left(x+1\right)^2}\)= Abs(x2-1) + \(\sqrt{2}\left(x+1\right)\)
Do VT = VP
x2+1 = Abs(x2-1) + \(\sqrt{2}\left(x+1\right)\)
=> \(\orbr{\begin{cases}x^2+1=\left(x-1+\sqrt{2}\right)\left(x+1\right)\\x^2+1=-\left(x-1+\sqrt{2}\right)\left(x+1\right)\end{cases}}\)
Giải Phương trình ta được x = \(\sqrt{2}\)